Advancing Open Recognition in Canada: Future Skills Center's Role in Supporting a Digitally-enabled Skills Ecosystem (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2026)
The presentation examined how the Future Skills Center (FSC) is advancing open recognition in Canada by funding and testing innovative approaches to skills recognition. FSC has invested in several initiatives focused on microcredentials, as well as many projects that deployed technology platforms to enable the issuance, exchange, and recognition of credentials. At the intersection of these project portfolios is a commitment to experimenting, learning, and gathering evidence on what works—and what does not—in building a more connected recognition ecosystem.  The presentation highlighted both progress and persistent challenges, including issues of design, interoperability, uneven stakeholder uptake, and access barriers. A key feature of the Canadian experience is regional and jurisdictional differences, which shape opportunities and constraints in distinct ways. This variability underscores both the complexity of creating a national approach and the importance of evidence-informed experimentation.  Based on our analysis, we offered insights on the lessons learned across the two key areas of our investment portfolio: investments to support the development and issuance of microcredentials and investments to develop and deploy technology platforms to solve skills-related challenges. Based upon our analysis, we outlined a vision for strengthening open recognition in Canada through more intentional articulation of change mechanisms and stronger alignment of incentives across different stakeholder groups.  By sharing FSC's work at the intersection of funding, experimentation, and policy context, this session contributed to ePIC 2025's theme by offering a grounded and forward-looking perspective on how innovation in open recognition can be nurtured and scaled in complex ecosystems.  Keywords: open recognition, microcredentials, skills ecosystems, digital credential platforms, policy experimentation